PRINCIPLES OF VILLAGE FUND MANAGEMENT WITH GOOD GOVERNANCE - Alvin, Ferry Andriyanto (Airlangga Development Journal, 2025)
This paper addresses the importance of village fund management in Indonesia, a significant challenge given the sheer number of villages, totaling tens of thousands across the archipelago. The implementation of Good Governance principles in village fund management is crucial to ensure transparency, accountability, participation, and efficiency in fund utilization. This research aims to investigate how these Good Governance principles are applied in the management of village funds in Indonesia. The research methodology includes policy document analysis, case studies of implementation in selected villages, and interviews with stakeholders. Findings indicate that while efforts are made to apply Good Governance principles, challenges remain in practice, such as limited transparency in decision-making, inadequate community participation in monitoring, and insufficient accountability in fund utilization. Recommendations for improvement include expanding public access to information, strengthening independent oversight mechanisms, and enhancing awareness and capacity regarding the importance of Good Governance at the village level. These steps are expected to enhance the effectiveness of village fund management and support sustainable development at the local level.